2006
DOI: 10.1080/09585190600878451
|View full text |Cite
|
Sign up to set email alerts
|

Management development practices: empirical evidence from Sri Lanka

Abstract: Being a South Asian developing country, management development (MD) practices in Sri Lanka has received insufficient attention. The paper reports results of an empirical investigation of 219 managers and 78 human resource (HR) managers on MD practices in Sri Lanka. The study investigated different processes by which MD takes place in organizations, the nature of immediate senior managers' support for MD, the importance given to the HRM function in the organizational strategy and the HR managers' contribution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Apart from the world-wide attention Sri Lanka received at the time of the tsunami disaster in December 2004, the country remains little explored in the scholarly world of management. While some research has been published in this context (Kumarasinghe & Hoshino, 2003;Chandrakumara & Sparrow, 2004;Mamman et al, 2006;Akuratiyagamage, 2007), and to the best of our knowledge, there is little or no research that has focussed on middle-management's perceptions of leadership, or on management practices and organizational performance in Sri Lanka. It is this gap in the literature that this paper seeks to fill.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the world-wide attention Sri Lanka received at the time of the tsunami disaster in December 2004, the country remains little explored in the scholarly world of management. While some research has been published in this context (Kumarasinghe & Hoshino, 2003;Chandrakumara & Sparrow, 2004;Mamman et al, 2006;Akuratiyagamage, 2007), and to the best of our knowledge, there is little or no research that has focussed on middle-management's perceptions of leadership, or on management practices and organizational performance in Sri Lanka. It is this gap in the literature that this paper seeks to fill.…”
Section: Introductionmentioning
confidence: 99%
“…If papers were context embedded, the selected context guided purpose of the research, which means that context information was used to highlight its significance to the selected phenomenon and/or theory. These studies also developed new scales in the selected context in order to collect the data because no scale was available in a similar context (Akuratiyagamage, 2006; Kopalle et al , 2010) or arrived at a new framework based upon their data analysis (Johnson and Tellis, 2008). We only included papers (in this category) that had developed all (and not one or two) scales for their data collection because we did not think that only a few context‐driven scales could help authors draw as meaningful implications as all scales would be able to (Wasti et al , 2007).…”
Section: Procedures For Content Analysis Of the Published Researchmentioning
confidence: 99%
“…That is to say, managers take better control of their learning and become more aware of and sensitive to contextual cues in the structural, systems and strategic processes of the organisation through their self-directed and inter-dependent learning and collaborative inquiry. As an example of the importance of informal learning processes, the study of Akuratiyagamage (2006) with both line managers and HR managers in 207 organisations in the manufacturing industry demonstrated that daily organisational experiences provide the most immediate and effective opportunity for management development. Such ongoing development experiences, when applied within the framework of action learning, provide further opportunities to develop a learning orientation for managers dealing with urgent and complex organisational issues which then actually become catalysts for reflective learning and action taking (Marquardt et al, 2009).…”
Section: Relevance Of Action Learning To Management Development Hrm mentioning
confidence: 99%
“…According to Lees (1992), management development encompasses the entire system of organisational activities aimed at improving the performance of managers or decision makers in significant ways going beyond mere education and training. Where management development consists of an integrated learning experience, the various processes are aimed at enhancing the cognitive and behavioural change of managers by focusing not only on their competence to handle day-to-day tasks, but on their level of commitment to creating greater value for the organisation (Akuratiyagamage, 2006). There are two underlying processes of management development, the informal and formal, that mutually reinforce in a well-designed management development strategy (Mole, 2000).…”
Section: Relevance Of Action Learning To Management Development Hrm mentioning
confidence: 99%